Synergic toxic effects of food contaminant mixtures in human cells. (18th August 2020) - Kopp, Benjamin; Sanders, Pascal; Alassane-Kpembi, Imourana; Fessard, Valérie; Zalko, Daniel; Le Hégarat, Ludovic; Audebert, Marc
Abstract: Humans are exposed to multiple exogenous substances, notably through food consumption. Many of these compounds are suspected to impact human health, and their combination could exacerbate their harmful effects. We previously observed in human cells that, among the six most prevalent food contaminant complex mixtures identified in the French diet, synergistic interactions between component appeared in two mixtures compared with the response with the chemicals alone. In the present study, we demonstrated in human cells that these properties are driven only by two heavy metals in each mixture: tellurium (Te) with cadmium (Cd) and Cd with inorganic arsenic (As), respectively. It appeared that the predicted effects for these binary mixtures using the mathematical model of Chou and Talalay confirmed synergism between these heavy metals. Based on different cell biology experiments (cytotoxicity, genotoxicity, mutagenesis and DNA repair inhibition experiments), a detailed mechanistic analysis of these two mixtures suggests that concomitant induction of oxidative DNA damage and decrease of their repair capacity contribute to the synergistic toxic effect of these chemical mixtures. Overall, these results may have broad implications for the fields of environmental toxicology and chemical mixture risk assessment.